(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2016)
يعد مفهوم العقلانية من أوفر المفاهيم الفلسفية حظاً فيما يتعلق بالاختلافات حوله، بل هو أشد المفاهيم عرضه للرفض أو النقد والتحليل، لذا فإن بحثنا محاولة في فض الإشكالية المتعلقة بضبط مصطلح العقلانية كمفهوم يشير إلى دلالات متعددة في حقبة الفلسفة الحديثة، التي تعد التأسيس الحقيقي لما وصل إليه العالم اليوم في كل مناحيه الفكرية والعلمية والاجتماعية. وتبعاً لهذا السياق الاصطلاحي والمفهومي حاولنا في البحث التركيز على تاريخية مفهوم العقلانية من خلال نشأتها وتطورها كاتجاه في الفكر الأوروبي الحديث، بوصفه الحامل لأولية العقل، منطلقاً من عدة معانٍ متكاملة حيناً ومتناقضة حيناً آخر، ليحمل بذلك دلالات متعددة، تتنوع بتنوع مجال استخدامه، وبشيء من التركيز حاولنا إبراز أهم المعاني التي يقال بها مصطلح العقلانية. علّنا بذلك نساهم في رفع الالتباس الذي لحق به، والذي كان سبباً في غموض المصطلح، وبالتالي سبباً لتشويش فهمنا لفلسفة الحداثة. Rationality is by far the luckiest philosophical concept in so far as its controversial status is concerned. It is also one of the terms most liable to rejection, criticism and analysis. Hence, our paper is an attempt to unscramble the controversy relating to tuning the term of rationality into a concept that denotes multiple significations in the era of modern philosophy, and which are considered the real foundation of what today’s world has reached in its intellectual, scientific and social aspects. According to this terminological and conceptual context, we have tried in this paper to shed special light on the genealogy of the concept of rationality, its origins and evolution as a trend in modern European thought, given that it is a signifier that denotes the priority of the mind, and which derives from various meanings that are complementary at times, yet contradictory at others, whereby carrying multiple significations, that vary in accordance with its field of use. With a certain degree of special attention, we have also tried to glean some of the most basic meanings associated with the term of rationality. We hope that this way we may be able to clarify the obscurity that engulfs the term, something which has caused its ambiguity, and thus our confused understanding of the philosophy of modernity